PENGARUH HARGA, KUALITAS PRODUK, DAN IKLAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK SIPPIN DI KOTA TANJUNGBALAI - Saputri Rambe, Aprilia Indah; Wardana, Ilham Tri; Simamora, Sri Ulfa; Ningsih Pasaribu, Silfira Ayu; Lubis, Nikmah Kholilah; Suhairi, Suhairi (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
This study aims to determine the direct effect of price perception on purchase decisions, the quality of service on purchasing decisions and social media advertising on purchase decision of the product Sippin in Tanjungbalai. The research strategy used is the strategy is associative. The population in this research is the consumer not the only one in the City of Tanjungbalai. Samples taken as many as 100 respondents who are consumers who buy the product Sippin while visiting outlate. The sampling technique used is simple random sampling with the instrument of data collection in the form of a list of questions. This research method using qualitative descriptive. The results of the research concluded price perception has a positive effect on the purchase decision. Service quality has a positive effect on purchasing decisions and social media advertising also has a positive effect on the purchase decision. Therefore the price perception, service quality and social media advertising has a positive effect on the purchase decision of the product not the only one in the City of Tanjungbalai.